Ordered Mesoporous Silica Monoliths as a Versatile Platform for the Study of Magnetic and Photomagnetic Prussian Blue Analogue Nanoparticles. Issue 10 (17th January 2017) - Moulin, Robinson; Delahaye, Emilie; Bordage, Amélie; Fonda, Emiliano; Baltaze, Jean‐Pierre; Beaunier, Patricia; Rivière, Eric; Fornasieri, Giulia; Bleuzen, Anne
Abstract : Ordered mesoporous silica monoliths were used as a versatile platform to study the effect of size reduction on the photomagnetic properties of the Rb2 Co4 [Fe(CN)6 ]3.3 · n H2 O Prussian blue derivative. Through the variation of the organization of the pores, the metal loading and the chemical composition of the solid matrix, it was possible to modify independently the aggregation state, the dilution and the chemical environment of the nanoparticles and to disentangle the effect of each parameter on the physical properties. The approach was first assessed by using the versatile platform to study the effect of size reduction on the magnetic properties of Prussian blue analogues, which were highly sensitive to dilution effects. Then, the approach was applied to photomagnetic nanoparticles. The photomagnetic effect in particles of nanometric dimensions is due to the photoinduced Co III (LS)Fe II →Co II (HS)Fe III electron transfer (LS = low spin, HS = high spin). The photomagnetic properties of nanoparticles are relatively insensitive to dilution effects, but the thermal relaxation of the photoexcited state is sensitive to the chemical environment of the nanoparticles. Abstract : The use of mesoporous silica as a matrix for the formation of nanoparticles of magnetic and photomagnetic coordination compounds enables the study of the properties of the compounds at the nanoscale owing to the versatility of the synthetic pathway.